Philosophy for teens : questioning life's big ideas - Kaye, Sharon M.; Thomson, Paul. (Waco, TX : Prufrock Press, 2007)
Covering a wide range of philosophical concepts, this volume address what are considered life's "big questions."
Includes glossary.
Keywords: Philosophy